FAKTOR EKSTERNAL DAN SIFAT INTERNAL SEBAGAI DASAR PERBAIKAN KEMASAN TRANSPORT BUAH SALAK - , Sri Sudarwati, Ir. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to detect external factor influence shaped pressure, storage temperature, storage time and vibration towards barking fruit internal character (tanin contents, water contents, sugar contents, acid contents, rate respiration, production ethylene, texture and dwindle heavy) and detect pressure influence and vibration towards barking fruit damage during transportation. Activity done in study transportation simulation that consist of fruit violence test and fruit vibration test. fruit is depressed up to achieved bruised level 0% (control), 25 % (112,5 N, 50 % (225 N) and 75 % (337,5 N) from maximal load that acceptable by fruit (450 N), furthermore fruit is kept in 3 temperature conditions that is in temperature 10oC, 20 oC and 25 oC. Observation is done in day storage to 0, to 2, to 4, to 6 and to 8. vibration test is done by, as much as 10 kg barking fruit in the size carton 35 x 24 x 23 cm. Fruit furthermore done vibration with frequency 150 vibrations per minute during 24 clocks. sample observation is done with time interval 0 clocks, 3 clocks, 6 clocks, 9 clocks, 12 clocks, 15 clocks, 18 clocks, 21 clocks and 24 clocks. parameter that watched to cover tanin contents, water contents, sugar contents, acid contents, rate respiration, production ethylene, dwindle heavy and fruit network system. From this study result shows that pressurizing, storage temperature, long storage and tall vibration can demote tanin contents, water contents, sugar contents, acid contents, rate respiration, production ethylene and fruit texture, but cause in increase dwindles heavy. Pressure and vibration inclined cause barking fruit network that is parenchym, cuticule and epydermis be to broken so that fast experience putrefaction. Pressurizing consequence fruit damage is accelerated with storage in tall temperature. Therefore during tranportasi necessary done correct packaging, good also ingredient that used that is by using primary package cell tray.